Design and Implement an EC-Application Based on Multi Database Environment - Hadi, S. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The vast majority of EC applications are the web-based deployed in 3-tire Server-Client environment, the data within such application often resides within several heterogeneous data sources. Building a single application that can access each data sources can be a matter of challenging; this paper concerns with developing a software program that runs transparently against heterogeneous environment for an EC-application.